Efficacy of metacognitive therapy for prolonged grief disorder: protocol for a randomised controlled trial - Wenn, J.; O'Connor, M.; Breen, L.; Kane, R.; Rees, Clare (2015)
Introduction: Studies of effective psychotherapy for individuals suffering from the effects of prolonged grief disorder (PGD) are scarce. This paper describes the protocol for an evaluation of a metacognitive therapy programme designed specifically for PGD, to reduce the psychological distress and loss of functioning resulting from bereavement. Methods and analysis: The proposed trial comprises three phases. Phase 1 consists of a review of the literature and semistructured interviews with key members of the target population to inform the development of a metacognitive therapy programme for Prolonged Grief. Phase 2 involves a randomised controlled trial to implement and evaluate the programme. Male and female adults (N=34) will be randomly assigned to either a wait list or an intervention group. Measures of PGD, anxiety, depression, rumination, metacognitions and quality of life will be taken pretreatment and posttreatment and at the 3-month and 6-month follow-up. The generalised linear mixed model will be used to assess treatment efficacy. Phase 3 will test the social validity of the programme. Discussion: This study is the first empirical investigation of the efficacy of a targeted metacognitive treatment programme for PGD. A focus on identifying and changing the metacognitive mechanisms underpinning the development and maintenance of prolonged grief is likely to be beneficial to theory and practice.